HUBUNGAN PAJANAN BENZENE DENGAN TEMUAN RETIKULOSIT, KADAR HEMOGLOBIN DARAH, DAN KADAR FENOL DALAM URINE PEKERJA INDUSTRI SEPATU X JAKARTA - Chairul Anwar Nasution; Ari Suwondo; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Benzene exposure through the use of glue could cause serious risks for the human body. One of the target organ of benzene exposure was the bone marrow. Chronic effects of benzene exposure was damage to the blood formed system, such as damaged to the bone marrow, caused a decrease in blood cell counts. Phenol urine could be used as an indicator of exposure to benzene. The purpose of this study was to determine the correlation between benzene exposure by reticulocytes, hemoglobin, and urine phenol shoe industry. This study used a quantitative method with cross sectional approach. Population and sample of 30 people who were determined by the total sampling method. The results of the study by Chi Square test showed that there was no correlation between the concentrations of benzene-reticulocytes (p-value = 1.000), work period-reticulocytes (p-value = 1.000), retikulosit- hemoglobin (p-value = 1.000), the concentration of benzene -hemoglobin (p-value = 0.304), work period-hemoglobin (p-value = 1.000), urine concentrations of benzene-phenol (p-value = 1.000), and work period-phenol urine (p-value = 1.000). Factors that determined the results of the study include the relatively concentrations of benzene, continuity of exposure, phenol urine test was not specific and sensitive. Researchers suggest that the industry owners should always use PPE at work, and conducted periodic health examinations. For further research to measured the concentration of benzene with personal sampling, use a urine test was more specific and sensitive, and use the study cohort in the study area.